EFEKTIVITAS APLIKASI TRANSPORTASI GOJEK DENGAN MENGGUNAKAN METODE SYSTEMATIC LITERATURE REVIEW - Khoirul Adib; Guntur Syarifuddin Putra; Siti Nur`aini (Jurnal Teknik Informatika dan Teknologi Informasi, 2022)
The rapid development of the field of information technology has made a lot of transformations, especially in the field of online transportation services, many business actors providing transportation services are emerging today, so there is a lot of competition between online transportation service providers with various strategies in order to satisfy customers. Currently, there are many studies examining online transportation. So there is a need for a review of journal papers that discuss the effectiveness of online transportation, but in this study it is devoted to the Gojek application because it is felting that it is widely used by the Indonesian people. The method used is the Systematic Literature Review (SLR) of journal papers published in 2019-2022. There are three Research Questions in this study. The end result is that the Gojek application has several features that make it easier for people to use it. In the technique of collecting data using questionnaires from previous studies with the use of at most 100 respondents. And there are 6 factors that make people choose Gojek online transportation for activities with the most being chosen because the quality of services and services provided by Gojek is very good. The final result of this research is to provide information related to the results of community responses in several areas so that it can be used as a joint evaluation material, especially for Gojek transportation.